Genome resources and whole genome resequencing of Phytophthora rubi isolates from red raspberry - Sapkota, Sanjib; Burlakoti, Rishi R.; Lubberts, Mark; Lamour, Kurt (Frontiers in Plant Science, 2023)
Phytophthora rubi is a primary causal agent of Phytophthora root rot and wilting of raspberry (Rubus idaeus L.) worldwide. The disease is a major concern for raspberry growers in Canada and USA. To date, no information is available on genomic diversity of P. rubi population from raspberry in Canada. Using a PCR-free library prep with dual-indexing for an Illumina HiSEQX running a 2x150 bp configuration, we generated whole genome sequence data of P. rubi isolates (n = 25) recovered during 2018 to 2020 from nine fields, four locations and four cultivars of raspberry growing areas of British Columbia, Canada. The assembled genome of 25 isolates of P. rubi averaged 8,645 scaffolds, 303× coverage, and 69,607,200 bp. We exploited single nucleotide polymorphisms (SNPs) obtained from whole genome sequence data to analyse the genome structure and genetic diversity of the P. rubi isolates. Low heterozygosity among the 72% of pathogen isolates and standardized index of association revealed that those isolates were clonal. Principal component analysis, discriminant analysis of principal component, and phylogenetic tree revealed that P. rubi isolates clustered with the raspberry specific cultivars. This study provides novel resources and insight into genome structure, genetic diversity, and reproductive biology of P rubi isolated from red raspberry. The availability of the P. rubi genomes also provides valuable resources for future comparative genomic and evolutionary studies among oomycetes pathogens.